Detection of Aflatoxin B1 among Early and Middle Childhood Iraqi Patients (Baghdad Science Journal, 2020)
The study was conducted for the detection of Aflatoxin B1(AFB1) in the serum and urine of 42 early and middle childhood patients (26 male and 16 female ) with renal function disease, liver function disease, in additional to atrophy in the growth and other symptoms depending on the information within consent obtained from each patient, in addition to 8 children, apparently healthy, as the control. The technique of HPLC was used for the detection of AFB1 from all samples. The results showed that out of 42 patient children, 19 (45.2%) gave positive detection of AFB1 in the serum among all age groups patients with a mean of 0.88 ng/ml and a range of (0.12-3.04) ng/ml. This was compared with the control that did not detect any level. On the other hand, AFB1 was not detected in any of urine samples in both of the sexes. Positive results of serum AFB1 were recorded in males more than females sample which reached 12(46.1%) and 7(43.7%) respectively with a mean/ range reached to (1.08 /0.12-2.91 and 0.82/0.12-1.30)ng/ml respectively, compared with 8 control samples that did not detect any value of aflatoxins.